Platelet-activating factor receptor antagonists of natural origin for acute ischemic stroke: a systematic review of current evidence - Li, Tingting; Zhang, Xuebin; Jiang, Ping; Zhang, Dandan; Feng, Luda; Lai, Xinxing; Qin, Mingzhen; Wei, Yufei; Zhang, Chi; Gao, Ying (Frontiers in Pharmacology, 2022)
Background: Acute ischemic stroke (AIS) is a common cause of death and long-term disability worldwide. Recent trials of platelet-activating factor receptor antagonists (PAFRA) appeared to indicate that they could play a neuroprotective role in the treatment of AIS; therefore, we conducted a systematic literature review to evaluate the clinical efficacy and safety of PAFRA in patients with AIS. Methods: A systematic literature search was performed in seven electronic databases from inception to 11 March 2022. All randomized controlled trials (RCTs) in which patients were treated with PAFRA strategies within 7 days of stroke onset were included. Modified Rankin Scale (mRS) was selected as the primary outcome of this systematic review. The methodological quality of included studies was assessed based on the Cochrane Collaborations tool. The review protocol was previously registered (PROSPERO CRD42020182075). Results: Fifteen RCTs comprising a total of 3,907 participants were included in this study. The PAFRA-related compounds included natural preparations of terpenoids, flavonoids, and saponins, namely, ginkgo endoterpene diester meglumine (GEDM, seven RCTs), ginkgo biloba dropping pill (GBDP, one RCT), ginkgolide injection (GDI, four RCTs), hesperidin (HES, one RCT), ginsenoside Rd injection (GSRI, one RCT), and hydroxysafflor yellow A (HSYA, one RCT). All studies were conducted in China between 2017 and 2021, employing a two-arm parallel design with sample sizes ranging from 40 to 1,113. Eight studies (53.3%) provided no information on their method of randomization, and only two studies (13.3%) utilized the double-blind design. Treatment was associated with improved clinical outcomes for (1) GEDM, GDI, and GBDP in patients treated with conventional treatment (CM) [GEDM + CM for AIS on mRS: MDmRS = −0.42, 95% CI (−0.47, −0.37), five trials, p < 0.00001; GEDM + CM for AIS on NIHSS: MDNIHSS = −1.02, 95% CI (−1.51, −0.52), four trials, p < 0.0001]; (2) GEDM and GDI in patients treated with neuroprotective agent (NPA) [GEDM + NPA + CM for AIS on mRS: MDmRS = −0.40, 95% CI (−0.54, −0.26), p < 0.00001; GEDM + NPA + CM for AIS on NIHSS: MDNIHSS = −3.93, 95%CI (−7.72, −0.14), p = 0.04]; (3) GBDP in patients treated with CM; (4) GDI and GSRI in patients treated with IV rt-PA therapy (IVT); and (5) HSYA in patients compared with Dengzhan Xixin injection (DZXXI). No access to improved clinical outcome was associated with HES in patients treated with IVT. Seven RCTs reported adverse events (AEs) but found that taking PAFRA-related preparations was not associated with an increased incidence of AEs. Conclusions: This systematic review not only makes an important contribution to the existing body of current evidence but also lays a well-conducted basis for providing opinions and recommendation on the evaluation of PAFRA-based medicine, which could also highlight the need for well-designed clinical trials of PAFRA for AIS to increase the quality of available evidence. Further research is required, using standardized functional outcome measures for AIS, adequate blinding and suitable comparator groups reflecting current best practice.